How to realise a homogeneous dipolar Bose gas in the roton regime (data) - Juhász, P; Krstajić, M; Strachan, D; Gandar, E; Smith, R P (University of Oxford, 2022)
Data used in the publication "How to realise a homogeneous dipolar Bose gas in the roton regime" by Juhász et al., published in Physical Review A. The readme.txt file gives a detailed explanation of the data and its structure, the data itself are contained in the data.json file.